A COMPARATIVE STUDY OF PAREMIAS IN THE UZBEK AND ENGLISH LANGUAGES (A CASE STUDY OF SAYINGS) - Zayniddinova Irodaxon Botirjon kizi (International Journal of Literature and Language Studies, 2026)
The article offers a comparative semantic and linguocultural analysis of sayings (matal) in the Uzbek and English languages. We determine the degree of semantic equivalence between sayings and classify them into full, partial and non-equivalent (lacunar) units. We argue that the degree of equivalence depends primarily on the origin of the image: an internationally shared image yields full correspondence, whereas a nationally bound image yields partial or lacunar correspondence. The novelty of the study lies in placing the saying, as a distinct paremiological category, at the centre of comparison.